HAMBATAN KOMUNIKASI PENDAMPING SOSIAL - Imam Alfi; Dedi Riyadin Saputro (al-Balagh : Jurnal Dakwah dan Komunikasi, 2018)
The role of social assistant is very urgent in the implementation of social assistance programs, social security and social assistance. Citizen assistance is carried out through the Family Capability Improvement Program (P2K2), the activity is called Family Development Session (FDS). This article focuses on the problems that occur in these social assistance activities, especially in the communication barriers between social facilitators and citizens as Beneficiary Families (KPM). The study was conducted based on relevant literature. It was found that active and efficient communication became the determining factor in the implementation of community assistance. An affective strategy needs to be prepared in the assistance of beneficiary citizens so that the program is effective smoothly and efficiently.